Impact of abusive supervision on counterproductive work behaviors of nurses. (2nd July 2019) - Low, Yoke May; Sambasivan, Murali; Ho, Jo Ann
Key points: Abusive supervision does have impact on CWB. Perception of injustice leads to CWB. Abusive supervision directly and indirectly (through perception of injustice) leads to CWB. Power distance orientation of nurses moderates the relationship between abusive supervision and perception of injustice. Locus of control of nurses moderates the relationship between perception of injustice and CWB. Abstract : The objectives of this research are to address the two fundamental research questions: 1) What are the antecedents that lead to counterproductive work behavior (CWB) of nurses in public hospitals? 2) How effective are the moderating roles of power distance orientation (a cultural factor) and locus of control (an individual factor) in impacting CWB? The antecedents addressed are abusive supervision and nurses' perception of injustice. A questionnaire‐based study was conducted among 337 nurses working in six public hospitals in different departments in Malaysia. The data were analyzed using structural equation modeling. The main findings are:1) nurses perceive injustice when subjected to abusive supervision and indulge in CWB; 2) nurses with a high level of power distance orientation are less likely to perceive abusive supervision as injustice; and 3) nurses with an internal locus of control are less likely to engage in CWB. The contributions of the study are discussed.